Tinjauan Ancaman dan Solusi Keamanan pada Teknologi Internet of Things - Warsun Najib; Selo Sulistyo; Widyawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Internet of Things (IoT) is a well-known technology globally, which helps to connect things such as sensors, vehicles, hospital-instruments, industries, and consumer-goods through the internet. Compact smart devices constitute an essential part of IoT. They range widely in use, size, computing resources, and memory. However, integrating these intelligent things into the internet introduces several security challenges, because most internet technologies and communication protocols were not designed specifically to support IoT. Moreover, IoT's commercialization has led to public security concerns, including personal privacy issues, threats of cyberattacks, and organized crime. This review aims to provide a comprehensive list of IoT vulnerabilities and counter-measures against them. To achieve this goal, we first describe three widely-known IoT reference models and define security in the context of IoT. Second, we discuss the potential motivations of the attackers who target this technology. Third, we discuss different attacks and threats. Fourth, we describe possible countermeasures against these attacks. Finally, we describe emerging security challenges in IoT system.